Prospecting Through TEM Analyis of Metallic Nanoparticles in Groundwater - Fitzpatrick, William A.; Hooper, Robert L. (My University, 2018)
With the search for new deposits of metallic resources pushing prospecting into increasingly poorly exposed areas, this project aims to test an experimental prospecting technique developed in China to discover potential zones of mineralization in areas where host units may have little to no outcrop. Potential detection of metallic ore bodies is achieved through TEM analysis of nanoparticles within groundwater samples collected in an area of interest, with their characteristics providing evidence for the existence of an ore body located at depth. To verify this method, groundwater samples have been collected from two areas with known metallic deposits, the eagle mine in the Upper Peninsula of Michigan and the Kingston Mining district in New Mexico. Initial results have shown a positive correlation of metals in nano-particle chemistry from areas of mineralization. In samples from the eagle mine, metallic components of nanoparticles include Cr up to 10,000ppm, Zn up to 22,000ppm and Co up to 620ppm while analyses of nanoparticles within Kingston groundwater reveal a large component of Zn from 5-13%. If this method continues to show promise, it could be used in a future project to provide evidence for or against existence of an ore body in a targeted location, possibly in combination with other prospecting methods such as hydrogeochemistry.
Color poster with text, charts, images, and graphs.
Keywords: Nanoparticles; Metals; Transmission electron microscopy; Posters